2011
DOI: 10.17221/1558-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a porcine sapovirus strain isolated from a piglet with diarrhoea: a case report

Abstract: Porcine sapoviruses, members of the family Caliciviridae, have been considered as an aetiological agent of gastroenteritis in pigs. In this study, we analysed 251 faecal samples obtained from 3 to 90 day-old diarrhoeic pigs in the Czech Republic between January 2005 and June 2010 and tested them by negative staining electron microscopy for the presence of sapoviruses. Only one sample showed the presence of viral particles with characteristic sapovirus morphology. The presence of sapovirus (SaV) was confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Second, we did not test the piglet samples for detecting bacterial pathogens (e.g. Escherichia coli ) and other viruses (porcine epidemic diarrhoea virus, porcine norovirus, porcine sapovirus, porcine astrovirus, transmissible gastroenteritis virus) which are also causing diarrhoea in piglets (Chen, Knutson, Rossow, Saif, & Marthaler, ; Dufkova, Kulich, & Prodelalova, ; Kumthip et al, ; Pizzurro et al, ; Shen et al, ). However, our study detected rotavirus among all samples of piglets ( n = 36) and study results suggested rotavirus was the primary cause of diarrhoea in piglets in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not test the piglet samples for detecting bacterial pathogens (e.g. Escherichia coli ) and other viruses (porcine epidemic diarrhoea virus, porcine norovirus, porcine sapovirus, porcine astrovirus, transmissible gastroenteritis virus) which are also causing diarrhoea in piglets (Chen, Knutson, Rossow, Saif, & Marthaler, ; Dufkova, Kulich, & Prodelalova, ; Kumthip et al, ; Pizzurro et al, ; Shen et al, ). However, our study detected rotavirus among all samples of piglets ( n = 36) and study results suggested rotavirus was the primary cause of diarrhoea in piglets in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the virus cannot be excluded as a causative or contributor agent of diarrhoea because studies have associated the presence of porcine SaV with enteric disease (Kim et al 2006;Martella et al 2008;Zhang et al 2008;Dufkova et al 2011). Porcine SaV has also been reported in mixed infections with porcine norovirus Scheuer et al 2013), Aichivirus C and/or porcine astrovirus (Dufkova et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine SaV belongs to the genogroup GIII and is represented by the prototype Cowden strain . Based on genetic variability of the porcine SaV, the GIII genogroup can be divided into three lineages: 1, 2 and 3 (Collins et al 2009;Reuter et al 2010;Dufkova et al 2011). Novel porcine sapovirus genogroups have been proposed based on the capsid gene (GVI, GVII and GVIII) or the RdRp region (GIX?…”
Section: Introductionmentioning
confidence: 99%
“…Human SaV (HuSaV) strains are included within genogroups GI (genotypes GI.1-GI.8), GII (genotypes GII.1-GII.8), GIV (genotype GIV.1), and GV (genotypes GV.1 and GV.2) ( Farkas et al , 2004 ; Katayama et al , 2004 ; Reuter et al , 2010 ; Dufkova et al , 2011 ; Shibata et al , 2015 ; Diez-Valcarce et al , 2018 ; Xue et al , 2019 ). Pigs are infected by genogroups GIII, GV, GVI, GVII, GVIII, GIX, GX, and GXI ( Wang et al , 2005 ; Nakamura et al , 2010 ; Reuter et al , 2010 ; Dufkova et al , 2011 ; Kuroda et al , 2017 ; Diez-Valcarce et al , 2018 ) and dogs by genogroup GXIII ( Kuroda et al , 2017 ; Diez-Valcarce et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%